CEGAH PENINGKATAN KASUS COVID-19 MELALUI VIDEO EDUKASI ADAPTASI KEHIDUPAN BARU MASA PANDEMI DI LINGKUNGAN SEKOLAH - Ni Kadek Muliawati; Ni Luh Gede Puspita Yanti; Ni Putu Wiwik Oktaviani; Nurul Faidah; I Made Sudarma Adiputra (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Adaptation to New Habits (IMR) is an effort to accelerate the handling of Covid-19 that supports the sustainability of the community's economy that synergizes health, social and economic aspects. This educational video on adapting new habits in the school environment aims to increase school children's knowledge about adapting new habits during the covid 19 pandemic. The activity method used in this activity is counseling, demonstrations, and question and answer. This activity was attended by 11 students appointed by the school to take part in online activities via Zoom media. The questionnaire was given at the beginning of the meeting related to students' knowledge about adapting new habits at school and then providing an explanation of adapting new habits at school using video. At the end of the session, there was a demonstration on the correct point of adapting new habits and then continuing to fill out the questionnaire. Most of the students were at the age of 15 years, as many as 6 people (55%) of the total 11 students who took part in the activity. The results of the knowledge pretest obtained data from 4 students (36.4%) in the good category, 2 students (18.2%) in the sufficient category and 5 students (45.5%) in the poor category. The results of the posttest knowledge obtained data from 9 students (81.8%) in good category, 2 students (18.2%) in sufficient category and none in the less category. There is an increase in students' knowledge after being given education about adapting new habits at school with video media. Cooperation can be carried out with the Puskesmas to support information dissemination activities carried out consistently and sustainably